Cyber threat analysis of people and organizational processes in critical submarine infrastructure - Julkunen, Petro (2025)
This thesis investigates cyber threats targeting critical submarine infrastructure (CSI). The study focuses on people and organizational processes of operators of submarine telecommunications cables, power cables, and gas pipelines critical to Europe’s energy transmission and data communication. The thesis outlines the cyber threat landscape, identifies vulnerabilities associate to people and processes, and estimates potential impacts.